2010
DOI: 10.1088/2041-8205/721/2/l168
|View full text |Cite
|
Sign up to set email alerts
|

On THE REALITY OF THE SUGGESTED PLANET IN THE Ν OCTANTIS SYSTEM

Abstract: The aim of this study is to explore an enigmatic finding about the ν Octantis binary system that indicates the possible existence of a Jupiter-type planet even though the planet seems to be located outside the zone of orbital stability. We perform a detailed analysis of orbital stability based on previous studies that carefully considers the ν Octantis system parameters including their observationally deduced uncertainties. In our analysis, we confront the probability distribution of the parameter space of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 20 publications
2
61
0
Order By: Relevance
“…A prograde orbit has no stability, and the binary-secondary scenario proposed by Morais & Correia (2012) appears to be unsupported by the available orbital solutions. Therefore the only recognizable astrophysical scenario continuing to be consistent with all available data is a retrograde planet (Ramm et al 2009;Eberle & Cuntz (2010). Thus, the reality of a planet in this unusually tight binary system's geometry (a bin < 3 AU, a pl /a bin ∼ 0.5) has more credibility and, for the time being, becomes that much more controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prograde orbit has no stability, and the binary-secondary scenario proposed by Morais & Correia (2012) appears to be unsupported by the available orbital solutions. Therefore the only recognizable astrophysical scenario continuing to be consistent with all available data is a retrograde planet (Ramm et al 2009;Eberle & Cuntz (2010). Thus, the reality of a planet in this unusually tight binary system's geometry (a bin < 3 AU, a pl /a bin ∼ 0.5) has more credibility and, for the time being, becomes that much more controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The controversial geometry of ν Oct has been investigated with increasing depth beginning with Eberle & Cuntz (2010) and subsequently by Quarles, Cuntz & Musielak (2012) and Goździewski et al (2013). Goździewski et al explored the system in considerable detail and found that stable solutions consistent with the Ramm et al results existed but were confined to tiny regions of the phase space.…”
Section: Introductionmentioning
confidence: 99%
“…apl 0.25abin (Holman & Wiegert 1999;Ramm et al 2009;Eberle & Cuntz 2010;Andrade-Ines et al 2016). However if the planet is in a retrograde orbit, as first suggested by Eberle & Cuntz (2010), the stability zone is wider (Jefferys 1974;Morais & Giuppone 2012), and places the conjectured orbit very near and perhaps within the boundary of stability. As extraordinary as the retrograde scenario may appear, since its very formation would also be challenged by strong dynamical interactions, the alternative standard explanations of instrumental or data reduction anomalies, starspots, pulsations or apsidal motion of the binary orbit are less supported by the observational evidence (Ramm et al 2009;Ramm 2015 5.81 ± 0.12 (6) T eff (K) 4 860 ± 40 (6) log g (cgs)…”
Section: Introductionmentioning
confidence: 83%
“…For a prograde orbit, models predict long-term stability should be limited to about half this distance i.e. apl 0.25abin (Holman & Wiegert 1999;Ramm et al 2009;Eberle & Cuntz 2010;Andrade-Ines et al 2016). However if the planet is in a retrograde orbit, as first suggested by Eberle & Cuntz (2010), the stability zone is wider (Jefferys 1974;Morais & Giuppone 2012), and places the conjectured orbit very near and perhaps within the boundary of stability.…”
Section: Introductionmentioning
confidence: 97%
“…Another example for significantly increased stability limits for retrograde orbits has been given by Eberle & Cuntz (2010b). They pursued a theoretical investigation of a previous observational finding about the ν Octantis binary system (Ramm et al 2009) that indicates the possible existence of a Jupiter-mass planet, although the planet appears to be located outside the zone of orbital stability.…”
mentioning
confidence: 99%